Development and Evaluation of a Yoga Training Program on Five-Dimensional Happiness in Elderly Individuals in Phu Rua Municipality - Yingyongwathanakit, Jeeranun (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
Globally and in Thailand, population aging has become a prominent demographic transition. Elderly residents in Phu Rua Municipality, Loei Province, experience substantial health burdens related to chronic non-communicable diseases and psychosocial problems. Yoga is recognized as an appropriate holistic exercise for the elderly; however, limited research has examined its effects on multidimensional well-being in rural community settings. This study aimed to (1) develop a yoga program tailored for rural community-dwelling elderly, and (2) evaluate its effectiveness on the Five Dimensions of Happiness: Physical Comfort (Suk Sabai), Joy (Suk Sanuk), Dignity (Suk Sa-nga), Wisdom (Suk Sawang), and Serenity (Suk Sa-ngob). This study employed a Research and Development (R&D) design in two phases. Phase 1 involved developing the yoga program through collaboration with a panel of 10 experts. Phase 2 used a quasi-experimental design with a pretest-posttest control group. A total of 82 elderly participants were randomly allocated into an experimental group (n = 41) and a control group (n = 41). The experimental group participated in a 12-week yoga program (once weekly supervised plus 3-4 home sessions). Outcomes were assessed using standardized measures of physical fitness, quality of life (WHOQOL-BREF-THAI), self-esteem (Rosenberg Self-Esteem Scale), cognitive function (TMSE), and mental health (Thai Mental Health Index). Data were analyzed using descriptive statistics and Analysis of Covariance (ANCOVA), adjusting for pre-test scores as covariates. The experimental group demonstrated significantly higher post-test scores across all five dimensions of happiness compared with the control group after adjusting for pre-test scores (p < .001 for all measures). Physical fitness indicators (Back Scratch, Chair Stand Test, Agility Course, Step Up and Down), quality of life, self-esteem, cognitive function, and mental health index scores were all significantly superior in the experimental group. Effect sizes ranged from large to very large (Partial η² = .462-.972). The developed yoga program is an effective intervention for enhancing holistic well-being among community-dwelling elderly and supports the promotion of active aging in rural settings.